Game theory and public policy - McCain, Roger A. (Cheltenham, UK : Edward Elgar, 2009)
'Game theory is useful in understanding collective human activity as the outcome of interactive decisions. In recent years it has become a more prominent aspect of research and applications in public policy disciplines such as economics, philosophy, management and political science, and in work within public policy itself. Here Roger McCain makes use of the analytical tools of game theory with the pragmatic purpose of identifying problems and exploring potential solutions in public policy.'--BOOK JACKET.
Pt. I. Historical and critical survey -- 1. Objectives and scope of the book -- 2. Representing games -- 3. A brief interpretive history of game theory -- 4. Nash equilibrium and public policy -- 5. Correlated equilibrium -- 6. Non-cooperative sequential games and public policy -- 7. Social mechanism design -- 8. Superadditive games in coalition function form -- 9. Imperfect recall and aggregation of strategies -- 10. Strategy, externality, and rationality -- Pt. II. Encapsulated cooperation -- 11. Coalition formation and stability -- 12. Bargaining, weak dynamics, and consensus -- 13. Formal aspects of games in partition function form -- 14. Coalitional play -- 15. The government game -- 16. Toward political economy.
Includes bibliographical references (p. 245-258) and index.
Keywords: Game theory; Policy sciences